Bax and Bak Pores: Are We Closing the Circle? - Cosentino, Katia (Trends Cell Biol, 2016)
Bax and its homolog Bak are key regulators of the mitochondrial pathway of apoptosis. On cell stress Bax and Bak accumulate at distinct foci on the mitochondrial surface where they undergo a conformational change, oligomerize, and mediate cytochrome c release, leading to cell death. The molecular mechanisms of Bax and Bak assembly and mitochondrial permeabilization have remained a longstanding question in the field. Recent structural and biophysical studies at several length scales have shed light on key aspects of Bax and Bak function that have shifted how we think this process occurs. These discoveries reveal an unexpected molecular mechanism in which Bax (and likely Bak) dimers assemble into oligomers with an even number of molecules that fully or partially delineate pores of different sizes to permeabilize the mitochondrial outer membrane (MOM) during apoptosis.